2023
DOI: 10.1002/jad.12244
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' social interaction skills on social media versus in person and the correlations to well‐being

Liron Lamash,
Yael Fogel,
Liat Hen‐Herbst

Abstract: IntroductionHigh‐quality social interactions with peers could protect adolescents' mental health, resilience, and well‐being. Assessing their social interaction skills (SIS) is essential to enhancing them. However, few instruments provide information about SIS in in‐person and social media environments. The SIS Questionnaire (SISQ) was developed to fill this gap, spotlighting adolescents' viewpoints on SIS in both environments. This study aimed to describe the SISQ development and psychometric properties, diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
4
1
Order By: Relevance
“…In this case, female adolescents who use social media more have lower life satisfaction. This is in contrast to a study by Lamash (2023), which found no significant correlation between age and happiness, and no gender differences related to happiness.…”
Section: Factors That Contribute To the Subjective Well-being Of Adol...contrasting
confidence: 99%
See 1 more Smart Citation
“…In this case, female adolescents who use social media more have lower life satisfaction. This is in contrast to a study by Lamash (2023), which found no significant correlation between age and happiness, and no gender differences related to happiness.…”
Section: Factors That Contribute To the Subjective Well-being Of Adol...contrasting
confidence: 99%
“…Furthermore, the findings of Lai et al, (2018) further explain that social media use is positively related to subjective well-being. According to the findings of Lamash (2023), there is a significant correlation between well-being and social interaction skills and social media use. This is reinforced by research by Zhang et al, (2023), which states that social media has a positive effect on psychological well-being (PWB) and subjective happiness (subjective well-being).…”
Section: Definition Of Social Media Usagementioning
confidence: 99%
“…The third approach invites more historical and system questions, ultimately concerning the notion of a “digital world” or “digital age,” as referred to in this commentary. Although more overarching than the relatively individualistic approach taken in this special issue, the transformations of a digital world can be discerned as motivations for research—consider Strohmeier et al's (2023) concern that adolescent girls do not fall behind the boys in the “digital career aspirations” needed for a digital society, or Lamash et al's (2023) assumption that, as social interactions become digitally mediated, new skills are required to ensure well‐being. Some discussions of artificial intelligence or the “metaverse” also raise the prospect of wholesale societal transformations.…”
Section: Last Wordsmentioning
confidence: 99%
“…Based on a sample of 1046 Italian students the findings suggested a potentially beneficial role of social media for those who are more socially anxious. In particular the absence of nonverbal cues (such as tone of voice or eye contact) was associated with a higher level of satisfaction with online communication among socially anxious students, while students with lower socially anxiety were more reliant on nonverbal cues.Social interaction skills were also the topic of the study by Lamash et al (2024) who developed an online questionnaire to measure adolescents' social interaction skills regarding both in-person and social media interactions and established their significant association with subjective wellbeing. The study by Van de Casteele et al (2024) identified satisfaction of basic psychological needs for autonomy, competence, and relatedness both offline and online as significant predictors of adolescent mental health, although offline need satisfaction played a more crucial role in their samples of adolescents and in particular among emerging adults in Belgium.Another set of studies address the role of interventions to support adaptive use of digital technologies.…”
mentioning
confidence: 99%
“…Social interaction skills were also the topic of the study by Lamash et al (2024) who developed an online questionnaire to measure adolescents' social interaction skills regarding both in-person and social media interactions and established their significant association with subjective wellbeing. The study by Van de Casteele et al (2024) identified satisfaction of basic psychological needs for autonomy, competence, and relatedness both offline and online as significant predictors of adolescent mental health, although offline need satisfaction played a more crucial role in their samples of adolescents and in particular among emerging adults in Belgium.…”
mentioning
confidence: 99%